Bio-refining of cottonseed meal from oil industry for the isolation of eco-friendly natural protein polymer - Babu Kayakada Murugesh; Tamrat Tesfaye; Fangong Kong (Zaštita Materijala)
Cottonseed meal (CSM) is a by-product of the oil industry. Globulins (salt soluble, vicilin, and legumin families) are the major dominant storage proteins in cottonseed and account for 60%-70% of seed proteins. However, these are unsuitable for human consumption due to their gossypol content. In this work, protein was extracted from defatted cottonseed flour with alkaline solution and its precipitation at different pH value was investigated. The crude protein was quantified using standard micro-Kjeldahl nitrogen method. Central composite design expert was conducted and the effect of variables in the extraction of protein were studied, namely, extraction solvent concentration, temperature and time. The optimum scheme of extraction was obtained at 0.1M NaOH with material to liquor ratio (MLR) 1:20 at pH 12 using temperature of 67℃ and a time of 90 min. Under these conditions, the response gives a flour dissolution percentage of 80.52% and protein purity percentage 80.40%. In addition, protein solubility and water absorption capacity were also determined and the chemical structure of protein was characterized by means of Fourier Transform Infrared Spectroscopy.